Social and Cultural Capital in Islamic Religious Education: Case Study of Madrasah Diniyah Nurul Huda Sarimulyo Blora - Shavira Rahmadani; Moh Yasir Alimi (Universitas Negeri Semarang, 2023)
Madrasah Diniyah Nurul Huda is a non-formal religious education that teaches Islamic religious sciences. This study aims to determine the forms of social and cultural capital in Madin Nurul Huda, the implications for institutions, students, teachers, the community around Madin Nurul Huda, and strategies to maintain social and cultural capital. This study used qualitative research methods. The research location is in Sarimulyo Village, Ngawen District, Blora Regency. Data collection techniques in this study are observation, interviews, and documentation. The theory is based on the theory of social capital and cultural capital from Pierre Bourdieu. The results of this study are social capital in Madin Nurul Huda, namely in the form of social networks, beliefs, values and norms. Cultural capital in Madin Nurul Huda takes the form of the human dimension, the object dimension, and the institutional dimension. For students it has positive implications because they get religious knowledge and form good morals, but the classical study method is applied, students become passive in learning. The implication for teachers is that it is not too influential for improving welfare. The implications for the surrounding community are getting additional jobs and fulfilling Islamic religious education facilities. Strategies for maintaining social and cultural capital from Madin Nurul Huda, namely Haul and Akhirussanah, Halal Bihalal, and maintaining the good quality of teachers. Suggestions for Madin Nurul Huda are to be open to expanding their social network, for Madin Nurul Huda Teachers need a variety of learning methods, and for the Blora and Provincial governments it is hoped that they will pay attention to the welfare of Madin Teachers in Indonesia.